A study of incidence and propensity of locoregional lymph nodes in clinically N0 cases of carcinoma of tongue - Deshmukh, Sunil D.; N. Sayyad, Farhin (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: Oral cavity cancer is the sixth most common cancer worldwide with a high prevalence in South Asia. Among the populations where tobacco chewing is not endemic, tongue is the most frequent subsite for intraoral cancer. Methods: The prospective observational study was done at our tertiary care centre on 50 patients. CECT neck was done in all the clinically N0 (zero) cases to know the extent of tumour and neck metastasis. Wide local excision with elective neck dissection (END) was done for all clinically N0 cases with 1 year follow-up. Results: Clinical examination had high false negatives, sensitivity of CT scan imaging=18/20×100=90%, positive predictive value of CT scan imaging=18/26×100=69.23% and diagnostic accuracy=40 (18+22)/50=80%. Significant association was found between neck lymph node metastasis and tumor thickness. No significant association was found between grade of tumor and metastasis. Conclusions: CECT neck help to delineate the extent of END in carcinoma of tongue. In early-stage squamous cell carcinomas of the tongue (T1 and T2), a tumour thickness >5 mm should be taken as an indicator for prophylactic neck dissection as it is significantly associated with subclinical metastasis. Hemiglossectomy should be preferred over partial glossectomy to achieve better locoregional clearance and in turn to reduce rate of local recurrence. Hemiglossectomy with prophylactic END followed by appropriate chemoradiotherapy reduces locoregional recurrences and improved overall survival rate in early stage I and II of oral tongue squamous cell carcinoma (OTSCC).